Initial Sequence Strategy for Constructive Heuristics Using Gantt Chart - Hattem Siraj; Bareduan, Salleh Ahmad (Research Progress in Mechanical and Manufacturing Engineering, 2022)
There are many ways that a sequence in a constructive heuristic can be interpreted. Factors on the sequencing will always affect directly by its own initial variable that it set by using a certain heuristic. The constructive heuristics of Nawaz, Enscore and Ham (NEH) introduced in 1983 has been a long-standing favourite among researchers and industry in order to solve a flowshop scheduling method. In fact, the NEH still being futher studied by many researchers to improve the heuristic performance. The idea of this study was to introduce a modified heuristics from NEH that is able to surpassed the makespan of the NEH heuristics by having a shorter makespan as the objective of the study. The modified heuristics used a new method to arrange the initial sequence. Using the modified heuristics, the best sequence possible was then selected to be compared against the NEH heuristics. Results were obtained using Microsoft Excel with the Taillard’s dataset to obtain the needed sequence for both heuristics and were compared using Gantt chart for better visualisation. The end results shows that modified heuristic was able to achieve a shorter makespan when compared to NEH heuristics with the specific sequence that yield a difference of between 3 to 4 percent in this study. Involving all the scope of the study it was able to have a shorter makespan. The result of the study can enable more sequence-based variable to be use in solving a flowshop scheduling problem.